Comparison between Mifepristone and Ulipristal acetate as an alternative to surgical management of uterine fibroids (Leiomyoma) in symptomatic patients of reproductive age group in Asian population - Kale, Ashish R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Present study was a randomised prospective observational study carried out at Ashakiran Hospital and IVF centre Pune, Maharashtra, India to evaluate the efficacy, safety, and quality of life by using Ulipristal acetate 10 mg and Mifepristone 25 mg daily doses to treat uterine fibroids of two subgroups involving fibroids <3 cm and fibroids 3 to 5 cm all are in reproductive age group with symptomatic in nature over 3 months. Methods: A total number of 40 patients were recruited in the study of which they were divided into two groups according to the size of the fibroid as <3cm and 3-5cm as seen on transvaginal as well as transabdominal ultrasound. Further they were randomly assigned to either mifepristone or ulipristal orally with each category having 10 patients each to assess changes in fibroid size, in symptomatic pain reduction, menorrhagia and in quality of life. Results: The 25-mg dosage of Mifepristone is shown to be a good and effective way of treatment in fibroids less than 3 cm in achieving 40% reduction in size and 50% reduction in menorrhagia as compared to Ulipristal 10 mg which acts better in other subgroup of size 3-5 cm of fibroids. Conclusions: Still larger RCTs are needed to study the long-term benefits of these drugs.